2012
DOI: 10.1038/ismej.2012.6
|View full text |Cite
|
Sign up to set email alerts
|

Microbes inside—from diversity to function: the case of Akkermansia

Abstract: The human intestinal tract is colonized by a myriad of microbes that have developed intimate interactions with the host. In healthy individuals, this complex ecosystem remains stable and resilient to stressors. There is significant attention on the understanding of the composition and function of this intestinal microbiota in health and disease. Current developments in metaomics and systems biology approaches allow to probe the functional potential and activity of the intestinal microbiota. However, all these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
439
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 565 publications
(464 citation statements)
references
References 64 publications
20
439
0
5
Order By: Relevance
“…3 C and D). This result reinforces the concept that in vivo, A. muciniphila is primarily active as a mucin degrader (67) in contrast to B. acidifaciens, which is more versatile in its nutrient utilization strategy. The flexible foraging activity of B. acidifaciens raises the possibility that the presence of alternative nutrients could modify its activity in degrading host-derived compounds in the gut.…”
Section: Determining Compound Utilization Patterns Of Members Of the Gutsupporting
confidence: 87%
“…3 C and D). This result reinforces the concept that in vivo, A. muciniphila is primarily active as a mucin degrader (67) in contrast to B. acidifaciens, which is more versatile in its nutrient utilization strategy. The flexible foraging activity of B. acidifaciens raises the possibility that the presence of alternative nutrients could modify its activity in degrading host-derived compounds in the gut.…”
Section: Determining Compound Utilization Patterns Of Members Of the Gutsupporting
confidence: 87%
“…Ideally, human colonic mucins would be coated on the carrier materials using an agarindependent method. Next, Akkermansia muciniphila, the only known Verrucomicrobia representative that is a marker for mucin degradation (Belzer and de Vos, 2012), did not attain high densities in the current setup. Recent studies demonstrated that Akkermansia degrades mucins in (distal) colon regions characterized by depleted nutrient levels and long residence times (Van den Abbeele et al, 2010Abbeele et al, , 2011a.…”
Section: Discussionmentioning
confidence: 67%
“…Furthermore, as opposed to the luminal content where the pH was maintained constant, local accumulation of acids in mucus may cause a lower pH, selecting for Firmicutes over Bacteroidetes and Proteobacteria (Duncan et al, 2009). In addition, mucins may also serve as a growth substrate for butyrate-producing Firmicutes, possibly via cross-feeding with mucin-degrading microbes that deliver partial breakdown products, acetate and/or lactate (Belzer and de Vos 2012), similar as reported for fructo-oligosaccharides (Belenguer et al, 2006;Falony et al, 2006). Independent of the underlying reason, the mucus colonization by specific butyrate-producing Firmicutes (especially Clostridium cluster XIVa) species provides novel insight in the ecology of these abundant human gut colonizers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A. muciniphila may represent 3-5% of the microbial community (18,19) in healthy subjects, and its abundance inversely correlates with body weight (20)(21)(22)(23) and type 1 diabetes (24) in mice and humans, although a recent metagenomic study found that some of the genes belonging to A. muciniphila were enriched in type 2 diabetic subjects (25).…”
mentioning
confidence: 99%